2000
DOI: 10.1002/1098-1063(2000)10:5<617::aid-hipo13>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Spine loss and other dendritic abnormalities in epilepsy

Abstract: Studies of neurons from human epilepsy tissue and comparable animal models of focal epilepsy have consistently reported a marked decrease in dendritic spine density on hippocampal and neocortical pyramidal cells. Spine loss is often accompanied by focal varicose swellings or beading of dendritic segments. An ongoing excitotoxic injury of dendrites (dendrotoxicity), produced by excessive release of glutamate during seizures, is often assumed to produce these abnormalities. Indeed, application of glutamate recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(130 citation statements)
references
References 61 publications
(80 reference statements)
7
120
1
2
Order By: Relevance
“…Neuritic beading is observed in various pathological conditions (23)(24)(25)(26)(27)(28)(29)(30)(31). Our current results indicate that neuritic beads represent the accumulation of vesicular cargo and transport proteins following damage to the transport mechanisms by activated microglia.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Neuritic beading is observed in various pathological conditions (23)(24)(25)(26)(27)(28)(29)(30)(31). Our current results indicate that neuritic beads represent the accumulation of vesicular cargo and transport proteins following damage to the transport mechanisms by activated microglia.…”
Section: Discussionmentioning
confidence: 53%
“…Focal bead-like swelling in dendrites and axons (neuritic beading) is thought to be a neuropathological sign in ischemia (23), epilepsy (24), mechanical pressure (25), brain tumor (26), aging (27), and neurodegenerative diseases such as Alzheimer disease (28), Parkinson disease (29), and amyotrophic lateral sclerosis (30,31). Neuritic beading is also induced by various stimuli such as glutamate, nitric oxide (NO), 1 hypoxia, oxidative stress, glucose starvation, and hypotonic conditions (32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…Among a number of regulatory mechanisms controlling MAP2 function (see review, Sánchez et al, 2000), changes in calcium signaling, especially rises in intracellular calcium concentration ([Ca 2+ ] i ), have been most extensively studied following manipulations of synaptic inputs. Excessive glutamate receptor stimulation induced by physiological stimulation or exposure of glutamate or agonists of its receptors causes dendritic injury and/or MAP2 loss (Siman and Noszek, 1988;Bigot et al, 1991;Felipo et al, 1993;Arias et al, 1997;Faddis et al, 1997;Steward and Halpain, 1999;Swann et al, 2000;Vaillant et al, 2002). Recent studies in hippocampal slices further demonstrated that these changes are calcium-dependent (Hoskison and Shuttleworth, 2006;Hoskison et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Histological and retrograde tracer techniques have shown that kainate-induced epilepsy is associated with a dendritic sprouting of mossy fibers and new synapse formation in the dentate gyrus (Tauck and Nadler, 1985;Ben-Ari and Cossart, 2000;Wuarin and Dudek, 2001). However, the number of dendritic spines is reduced in other experimental seizure models (Swann et al, 2000), suggesting that epilepsy also can be linked to a partial deafferentation of cortical neurons.…”
Section: Changes Of Dendritic Structures In Epileptic Brainmentioning
confidence: 99%